Applications of Bioinspired Reversible Dry and Wet Adhesives: A Review - Kang, Minsu; Sun, Kahyun; Seong, Minho; Hwang, Insol; Jang, Hyejin; Park, Seongjin; Choi, Geonjun; Lee, Sang-Hyeon; Kim, Jaeil; Jeong, Hoon Eui (Frontiers in Mechanical Engineering, 2021)
Bioinspired adhesives that emulate the unique dry and wet adhesion mechanisms of living systems have been actively explored over the past two decades. Synthetic bioinspired adhesives that have recently been developed exhibit versatile smart adhesion capabilities, including controllable adhesion strength, active adhesion control, no residue remaining on the surface, and robust and reversible adhesion to diverse dry and wet surfaces. Owing to these advantages, bioinspired adhesives have been applied to various engineering domains. This review summarizes recent efforts that have been undertaken in the application of synthetic dry and wet adhesives, mainly focusing on grippers, robots, and wearable sensors. Moreover, future directions and challenges towards the next generation of bioinspired adhesives for advanced industrial applications are described.